2023
DOI: 10.1002/adem.202300572
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Elastic Conductive Yarn for Smart Textile Applications

Ravi Shekhar,
Nauman A. Choudhry,
Saniyat Islam
et al.

Abstract: Conductive yarns are crucial for electrical connections in electronic textiles and are used in fabricating sensors, electrodes, and wearable communication devices. Challenges in conductive and elastic properties of conductive yarns, their durability and compatibility with existing manufacturing processes limit mass production and affordability of conductive yarn. This work investigates elastic, shell‐conductive, and non‐corrosive electro‐conductive yarns (ECYs) for textile‐based wearable electronics. The exist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 69 publications
0
1
0
Order By: Relevance
“…Therefore, new interconnection structures and encapsulating methods need to be developed in order to improve the durability and maintain sensing accuracy for this kind of hybrid electronic yarn. Previous work has also shown that the helix structure is a common strategy for achieving the good stretchability of metal wire [ 13 , 14 , 15 ] while bonding technology with a conductive adhesive is a mature and applicable interconnection technology for producing printed flexible hybrid electronics [ 16 ]. In this way, the strategy combining the helix wire structure with bonding technology could potentially enable high mechanical durability and large-scale manufacturing for hybrid electronic yarn and then improve human motion flexibility, the working performance stability, and the service lifetime of smart garments or fabrics.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, new interconnection structures and encapsulating methods need to be developed in order to improve the durability and maintain sensing accuracy for this kind of hybrid electronic yarn. Previous work has also shown that the helix structure is a common strategy for achieving the good stretchability of metal wire [ 13 , 14 , 15 ] while bonding technology with a conductive adhesive is a mature and applicable interconnection technology for producing printed flexible hybrid electronics [ 16 ]. In this way, the strategy combining the helix wire structure with bonding technology could potentially enable high mechanical durability and large-scale manufacturing for hybrid electronic yarn and then improve human motion flexibility, the working performance stability, and the service lifetime of smart garments or fabrics.…”
Section: Introductionmentioning
confidence: 99%